A study on decision making in managing maintenance and building services in military organization - Awis, Ibrahim (2015)
Maintenance of assets particularly a building is an important as to maintain the high moral of soldiers and to uphold their standard of well-being. Poorly maintained buildings will somehow tarnish the image of Malaysian Armed Forces (MAF). Recently, the maintenance works carried out were questionable as there were many complaints among the occupants. This research was conducted with the aim to identify the management approach on decision making focusing on the servicemen and servicewomen who are lived in the military married quarters (RKAT) under 4 Briged Mechanize, Kem Batu 10, Kuantan, Pahang. The research objective is to identify the management approach on decision making and to evaluate the existing maintenance process, ultimately determine the relationship between independent variable and dependent variables. This study will focus on the management, housing condition and the maintenance work particularly on a military organization. This research aims to improve the value of buildings through a proactive maintenance and management system that is based on the concept of value for money. The methodology has made use of questionnaires to get the feedback from respondents for data collected to be unbiased and shared a common interest. The study come across useful information from data analysis that all the variables; decision making, building maintenance, quality maintenance and budget allocation have a degree of relationship, and the variables indicates that there are positively and negatively correlated each other’s. Thus, it signifies a moderate to strong positive relationship related with effective decision making.